A Review of Antidepressant Medications in the Treatment of Major Depressive Disorder: Effectiveness vs. Side Effects - Ahmad Khan; Hira Riaz; Maryam Noor (Research Journal of Psychology, 2025)
Background: Major depressive disorder (MDD) remains one of the most prevalent and disabling psychiatric illnesses worldwide. Pharmacological treatment options include selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), and monoamine oxidase inhibitors (MAOIs). Each class has unique efficacy and side effect profiles. Objective: This systematic review aimed to compare the effectiveness, tolerability, and safety of SSRIs, SNRIs, TCAs, and MAOIs for treating MDD in adults. Methods: A comprehensive literature search (2010–2022) was conducted across PubMed, Scopus, and Google Scholar to identify randomized controlled trials, observational studies, and meta-analyses evaluating efficacy and adverse effects. Data were extracted and analyzed descriptively; pooled effect sizes were calculated where appropriate. Results: SSRIs demonstrated the highest average effect size (Cohen’s d = 0.75), followed by SNRIs (0.68), TCAs (0.60), and MAOIs (0.55). Common side effects included sexual dysfunction and nausea with SSRIs and SNRIs, while TCAs and MAOIs were associated with sedation and weight gain. Younger men showed higher responsiveness but also reported more severe side effects. Conclusion: SSRIs remain the most effective and commonly prescribed treatment for MDD, though their side effect profile affects adherence. Personalized treatment approaches and further research are needed to optimize outcomes.